1988
DOI: 10.2186/jjps.32.1275
|View full text |Cite
|
Sign up to set email alerts
|

Bonding strength of the hardended plastic teeth to the denture base acrylic resin.

Abstract: We investigated the bonding strength of hardened plastic teeth to denture base acrylic resin. Two types of hardened plastic teeth conventional plastic teeth and porcelain teeth were used. As the denture base acrylic resin, conventional heat-curing type and heatcuring type containing 4-META adhesive monomer were used. Test specimens were fabricated under four tooth ridge lap treatments, 1) no treatment, 2) grinding, 3) monomer application, and 4) grinding and monomer application.Then bonding strengths were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…High-strength denture teeth have been developed, which retain some of the advantages of plastic teeth, such as easy occlusal adjustment and cost, while achieving improved hardness and abrasive wear resistance [1][2][3]. Findings of basic studies on these HS teeth have been reported in terms of impact resistance [4], bonding strength with denture base resin [5,6], hardness [1][2][3]5,6], and wear resistance of anterior teethm. However there seem to have been few studies on the abrasive wear resistance of posterior high-strength denture teeth [8.9].…”
Section: Introductionmentioning
confidence: 99%
“…High-strength denture teeth have been developed, which retain some of the advantages of plastic teeth, such as easy occlusal adjustment and cost, while achieving improved hardness and abrasive wear resistance [1][2][3]. Findings of basic studies on these HS teeth have been reported in terms of impact resistance [4], bonding strength with denture base resin [5,6], hardness [1][2][3]5,6], and wear resistance of anterior teethm. However there seem to have been few studies on the abrasive wear resistance of posterior high-strength denture teeth [8.9].…”
Section: Introductionmentioning
confidence: 99%